Pengaruh Penghasilan Rendah, Inflasi dan Total Penduduk pada Produk Domestik Bruto Regional Indonesia - Fadhillah Rahmi; Fitrawaty Fitrawaty; Muhammad Fitri Rahmadana (Ekonomis: Journal of Economics and Business, 2023)
Regional gross domestic product is the value of goods and services produced in that country in a given period. This study aimed to find out how low income, inflation and total population affect the regional gross domestic product. The research was conducted using a quantitative descriptive method. This study was conducted in 34 provinces in Indonesia between 2010 and 2020. The research sample was 34 provinces with an 11-year research period, so the results of observations in the study were 369 data. The data analysis used in this study was Panel Data Regression Analysis using Eveiws 9 software. The coefficient of determination test yielded a value of 0.866983 or 86.6983%, which means that the independent variables, namely low income, inflation and total population, can explain regional gross domestic product results. The results of the F test show that low income, inflation and total population significantly affect regional gross domestic product results. The t-test shows that low income positively and significantly affects the regional gross domestic product. In contrast, the inflation and total population variables have no effect on Indonesia's regional gross domestic product for the 2010-2020 period.